Dissolved Oxygen Control of Batch Bioreactor using Model Reference Adaptive Control scheme. Issue 4 (2018) - Chitra, M.; Pappa, N.; Abraham, Anuj
Abstract: Bioreactor imparts a significant role in the manufacture of pharmaceuticals, enzymes, food products, etc. as these processes depend on the biotransformation catalyzed by microorganisms. Dissolved Oxygen(DO) is one of the significant parameter in an aerobic fermentation process. DO control is difficult to achieve due to the variations in process dynamics during batch/fed-batch processes and the complex nonlinear behavior of the Bioreactor. In this paper, design and implementation of Model Reference Adaptive Control(MRAC) scheme based on MIT rule is applied to DO control of the bioreactor using the stirrer speed as control signal. A PC-supported, fully automated, multi-task control system has been designed and built by the authors using LabVIEW. A comparative study is carried out for the experimental bioreactor with conventional PI controller and proposed MRAC scheme for DO control. Results show that MRAC controller provides good tracking performance in comparison to PI controller.